Inhibition of breast cancer cells by targeting E2F-1 gene and expressing IL15 oncolytic adenovirus. Issue 7 (23rd July 2019) - Yan, Yang; Xu, Hu; Wang, Jiandong; Wu, Xin; Wen, Wei; Liang, Yan; Wang, Lingdi; Liu, Fengyuan; Du, Xiaohui
Abstract : The wide application of oncolytic adenovirus presents a novel therapeutic strategy for breast cancer gene therapy. Application of adenovirus alone achieves little curative effects on breast cancer. In addition, it is worth exploring the synergistic anti-tumor effect by inserting immunomodulatory factor in oncolytic adenovirus genome. By taking the advantage of the highly proliferative property of breast cancer, a novel recombinant adenovirus which could selectively kill tumor cells is established under an E2F-1 promoter. Also by carrying human Interleukin-15 (IL-15) gene, the oncolytic adenovirus exhibits an immunomodulatory effect. The present study proved that the novel oncolytic virus (SG400-E2F/IL-15) exhibits an enhanced anti-tumor activity both in vitro and in vivo, representing an experimental basis for breast cancer "virus-gene" therapy.